HOMER SIMPSON: PROTOTIPE SUPERHERO BARU AMERIKA - Danial Hidayatullah (Adabiyyāt: Jurnal Bahasa dan Sastra, 2009)
Hollywood films as one of America’s prominent industries that influence world’s popular culture can be seen as a cultural discourse. Movie as a popular literature conveys it message in its own unique ways. Myth is one of its messages. This study tries to reconstruct the myth of popular American superhero through an interesting new movie: The Simpsons.  How the new type of hero is manifested is analyzed in this study to find out the continuities or changes in American’s collective dreams so that the new American perspective over heroic mythologies can be understood. Basically this study analyzes as well the possibilities of the meanings conveyed by the media. Textual analysis is conducted to understand not only the meanings of the myth of the superhero perceived by the audience but also the American characters inside the myth. The Simpsons seems to offer a new type of hero’s myth, which is very distinct from the previous type of popular superheroes as in Batman, Superman, or Spiderman.